Zinc fertilization increases productivity and grain nutritional quality of cowpea (Vigna unguiculata [L.] Walp.) under integrated soil fertility management - Manzeke, Muneta G.; Mtambanengwe, Florence; Nezomba, Hatirarami; Watts, Michael J.; Broadley, Martin R.; Mapfumo, Paul (Elsevier, 2017)
Cowpea (Vigna unguiculata [L.] Walp.) is an important but under-studied grain legume which can potentially contribute to improved dietary zinc (Zn) intake in sub-Saharan Africa. In this study, surveys were conducted on smallholder farms in Zimbabwe during 2014/15 to determine the influence of diverse soil fertility management options on cowpea grain productivity and nutrition quality. Guided by the surveys, field experiments were conducted to investigate the influence of Zn fertilizer on the productivity and quality of cowpea under integrated soil fertility management (ISFM). Experiments were conducted on two soil-types, namely, sandy (6% clay) and red clay (57% clay) in 2014/15 and 2015/16 where cowpea was grown in rotation with staple maize (Zea mays L.) and fertilized with combinations of Zn, nitrogen (N), phosphorus (P) and two organic nutrient resources, cattle manure and woodland leaf litter. Cowpea grain yields on surveyed farms ranged from 0.3 to 0.9 t ha−1, with grain Zn concentration ranging from 23.9 to 30.1 mg kg−1. The highest grain Zn concentration was on fields where organic nutrient resources were applied in combination with mineral N and P fertilizers. Within the field experiments, mean grain yields of cowpea increased by between 12 and 18% on both soil types when Zn fertilizer was applied, from a baseline of 1.6 and 1.1 t ha−1 on red clay and sandy soils, respectively. When Zn fertilizer was co-applied with organic nutrient resources, grain Zn concentrations of cowpea reached 42.1 mg kg−1 (red clay) and 44.7 mg kg−1 (sandy) against grain Zn concentrations of 35.9 mg kg−1 and 31.1 mg kg−1 measured in cowpea grown with no Zn fertilizer on red clay and sandy soils, respectively. Agronomic biofortification of legumes is feasible and has the potential to contribute significantly towards increasing dietary Zn intake by humans. A greater increase in grain Zn of cowpea grown on sandy than red clay soils under Zn fertilization illustrates the influence of soil type on Zn uptake, which should be explored further in agronomic biofortification programs.